A presença do cotidiano durante a ditadura civil-militar argentina (1976-1983): a perspectiva infantil no filme Kamchatka (2002) - Pires Monteiro, Ygor (2021)
The article analyzes the argentine film Kamchatka (2002) from a dialogue with Bruno Groppo's work “The myth of society as a victim: post-dictatorial societies in the face of its past in Europe and Latin America”. In the film's plot, the protagonist is a 10-year-old boy, whose life is changed a few days after the 1976 coup d'état in Argentina due to the political militancy of his parents. As the work focuses on the daily life of the main character, it is possible to think about how cinema contributes to rethinking dichotomous memories built around social behaviors during the civil-military dictatorship, named by Groppo as the “myth of resistant society” and the “myth of innocent victim society". O artigo analisa o filme argentino Kamchatka (2002) a partir de um diálogo com o trabalho “O mito da sociedade como vítima: sociedades pós-ditatoriais em face de seu passado na Europa e na América Latina” de Bruno Groppo. No enredo do filme, o protagonista é um menino de 10 anos, cuja vida é alterada poucos dias após o golpe de Estado de 1976 na Argentina por conta da militância política dos pais. Como a obra se debruça sobre o cotidiano da personagem principal, é possível pensar como o cinema contribui para repensar memórias dicotômicas construídas em torno dos comportamentos sociais durante a ditadura civil-militar, nomeadas por Groppo como o “mito da sociedade resistente” e o “mito da sociedade vítima inocente”.